Imbalance of the renin–angiotensin system may contribute to inflammation and fibrosis in IBD: a novel therapeutic target?. Issue 5 (13th August 2019) - Garg, Mayur; Royce, Simon G; Tikellis, Chris; Shallue, Claire; Batu, Duygu; Velkoska, Elena; Burrell, Louise M; Patel, Sheila K; Beswick, Lauren; Jackson, Anvesh; Britto, Kaushali; Lukies, Matthew; et al.
Abstract : Objective: We evaluated the influence of the renin–angiotensin system (RAS) on intestinal inflammation and fibrosis. Design: Cultured human colonic myofibroblast proliferation and collagen secretion were assessed following treatment with angiotensin (Ang) II and Ang (1–7), their receptor antagonists candesartan and A779, and the ACE inhibitor captopril. Circulating and intestinal RAS components were evaluated in patients with and without IBD. Disease outcomes in patients with IBD treated with ACE inhibitors and angiotensin receptor blockers (ARBs) were assessed in retrospective studies. Results: Human colonic myofibroblast proliferation was reduced by Ang (1–7) in a dose-dependent manner (p<0.05). Ang II marginally but not significantly increased proliferation, an effect reversed by candesartan (p<0.001). Colonic myofibroblast collagen secretion was reduced by Ang (1–7) (p<0.05) and captopril (p<0.001), and was increased by Ang II (p<0.001). Patients with IBD had higher circulating renin (mean 25.4 vs 18.6 mIU/L, p=0.026) and ACE2:ACE ratio (mean 0.92 vs 0.69, p=0.015) than controls without IBD. RAS gene transcripts and peptides were identified in healthy and diseased bowels. Colonic mucosal Masson's trichrome staining correlated with Ang II (r=0.346, p=0.010) and inversely with ACE2 activity (r=−0.373, p=0.006). Patients with IBD who required surgery (1/37 vs 12/75, p=0.034) and hospitalisation (0/34 vs 8/68, p=0.049) over 2 years were less often treated with ACE inhibitors and ARBs than patients not requiring surgery or hospitalisation. Conclusions: The RAS mediates fibrosis in human cell cultures, is expressed in the intestine and perturbed in intestinal inflammation, and agents targeting this system are associated with improved disease outcomes.